Spatiotemporal mapping the neural correlates of acupuncture with MEG [corrected] [published erratum appears in J ALTERN COMPLEMENT MED 2008 Sep;14(7):889]. - Dhond RP; Witzel T; Hämäläinen M; Kettner N; Napadow V (Journal of Alternative & Complementary Medicine)
Acupuncture is an ancient Eastern healing modality with putative therapeutic applications. Unfortunately, little is known about the central mechanisms by which acupuncture may exert its effects. In this study, 15 healthy subjects were evaluated with magnetoencephalography (MEG) to map the location and timing of brain activity during low-frequency electroacupuncture (EA) and mechanical, noninsertive, sham acupuncture (SA) given at acupoint PC-6. Both EA and SA evoked brain responses that localized to contralateral primary somatosensory (SI) cortex. However, initial responses for EA peaked slightly earlier than those for SA and were located inferiorly within SI. Average equivalent current dipole strength was stronger (particularly at latencies >60 ms) for SA. These spatiotemporal differences between activations elicited by EA and SA are likely attributable to stimulus modality (electrical versus mechanical) and differences in the underlying somatosensory fibers transmitting these signals. The present data confirm that acupuncture modulates activity within somatosensory cortex, providing support for previous studies that suggest that the therapeutic effects of acupuncture are linked to SI modulation. Thus, MEG provides excellent spatiotemporal characterization of the somatosensory component of acupuncture, and future studies can contrast derived brain response parameters in healthy controls with those found in a diseased state.